Iron and the translation of the amyloid precursor protein (APP) and ferritin: riboregulation against neural oxidative damage in Alzheimer’s disease - Rogers, Jack (2008)
The essential metals iron, zinc and copper deposit near the Aβ (amyloid β-peptide) plaques in the brain cortex of AD (Alzheimer’s disease) patients. Plaque-associated iron and zinc are in neurotoxic excess at 1 mM concentrations. APP (amyloid precursor protein) is a single transmembrane metalloprotein cleaved to generate the 40-42-amino-acid Aβs, which exhibit metal-catalysed neurotoxicity. In health, ubiquitous APP is cleaved in a non-amyloidogenic pathway within its Aβ domain to release the neuroprotective APP ectodomain, APP(s). To adapt and counteract metal-catalysed oxidative stress, as during reperfusion from stroke, iron and cytokines induce the translation of both APP and ferritin (an iron storage protein) by similar mechanisms. We reported that APP was regulated at the translational level by active IL (interleukin)-1 (IL-1-responsive acute box) and IRE (iron-responsive element) RNA stem-loops in the 5′ untranslated region of APP mRNA. The APP IRE is homologous with the canonical IRE RNA stem-loop that binds the iron regulatory proteins (IRP1 and IRP2) to control intracellular iron homoeostasis by modulating ferritin mRNA translation and transferrin receptor mRNA stability. The APP IRE interacts with IRP1 (cytoplasmic cis-aconitase), whereas the canonical ferritin-H IRE RNA stem-loop binds to IRP2 in neural cell lines, and in human brain cortex tissue and in human blood lysates. The same constellation of RNA-binding proteins [IRP1/IRP2/poly(C) binding protein] control ferritin and APP translation with implications for the biology of metals in AD.